Differences in microbiological profile between community-acquired, healthcare-associated and hospital-acquired infections - Cardoso, T. (2013)
INTRODUCTION: Microbiological profiles were analysed and compared for intra-abdominal, urinary, respiratory and bloodstream infections according to place of acquisition: community-acquired, with a separate analysis of healthcare-associated, and hospital-acquired. MATERIAL AND METHODS: Prospective cohort study performed at a university tertiary care hospital over 1 year. Inclusion criteria were meeting the Centers for Disease Control definition of intra-abdominal, urinary, respiratory and bloodstream infections. RESULTS: A total of 1035 patients were included in the study. More than 25% of intra-abdominal infections were polymicrobial; multi-drug resistant gram-negatives were 38% in community-acquired, 50% in healthcare-associated and 57% in hospital-acquired. E. coli was the most prevalent among urinary infections: 69% in community-acquired, 56% in healthcare-associated and 26% in hospital-acquired; ESBL producers' pathogens were 10% in healthcare-associated and 3% in community-acquired and hospital-acquired. In respiratory infections Streptococcus pneumoniae was the most prevalent in community-acquired (54%) and MRSA in healthcare-associated (24%) and hospital-acquired (24%). A significant association was found between MRSA respiratory infection and hospitalization in the previous year (adjusted OR = 6.3), previous instrumentation (adjusted OR = 4.3) and previous antibiotic therapy (adjusted OR = 5.7); no cases were documented among patients without risk factors. Hospital mortality rate was 10% in community-acquired, 14% in healthcare-associated and 19% in hospital-acquired infection. DISCUSSION AND CONCLUSION: This study shows that healthcare-associated has a different microbiologic profile than those from community or hospital acquired for the four main focus of infection. Knowledge of this fact is important because the existing guidelines for community-acquired are